Jackson, The Prisoners 1914-1918 - Kennedy, W. Benjamin (Teaching History: A Journal of Methods, 1991)
Robert Jackson, former RAF pilot, military historian, and author of some fifty books, offers in this short work a sketch of the life of British POWs captured by the Germans during the Great War. Based on previously unpublished British prisoner narratives from the Imperial War Museum and some dozen or so similar accounts, most of which appeared in print soon after the war, the book relics on several long quotations from its sources to tell the story.